Perbedaan Tingkat Kemampuan Tentang Asessment Nyeri Wong Baker Scale Pada Perawat Yang Diberikan Edukasi Menggunakan Media Handout Dan Audiovisual - Putriantini, Erdya (Jurnal Keperawatan Muhammadiyah, 2024)
Pain is an unpleasant sensory and emotional experience resulting from tissue damage, either actual or potential. Pain assessment is important to determine the intensity and determine effective therapy. The general aim of this research is to determine the differences in ability levels regarding the Wong Baker Scale pain assessment between nurses who were given education using handouts and audiovisual media in the hemodialysis room at Dr. RSUD. Saiful Anwar Malang. This research method uses a Quantitative approach with a Pre-Experimental design with a One Shot Case Study approach which is divided into 2 groups, namely 13 respondents as the handout group and 13 respondents as the audiovisual group. The test for differences in ability levels between the handout and audiovisual groups used the Mann Whitney test with a P value of 0.011 (P < 0.05), meaning that there were differences in the level of ability for the Wong Baker Scale pain assessment among nurses who were given education using Handout and Audiovisual media in the Regional Hospital's Hemodialysis Room. Dr. Saiful Anwar Malang. In the Handout group, almost all 10 respondents (76.9%) were in the Good category, in the Audiovisual group, most of the 8 respondents (61.5%) were in the Fair category. Studying with handouts is more effective than audiovisual because it provides the opportunity to read and process information slowly, as well as re-access material that is difficult to understand. Respondents can take time to understand concepts carefully, while videos are too fast and difficult to stop or repeat.